2016
DOI: 10.1007/s00705-016-2882-z
|View full text |Cite
|
Sign up to set email alerts
|

Detection of the VP6 gene of group F and G rotaviruses in broiler chicken fecal samples from the Amazon region of Brazil

Abstract: The aim of this study was to detect rotavirus F (RVF) and rotavirus G (RVG) in fecal specimens of broiler chickens in Brazil. During 2008 and 2011, a total of 85 fecal samples were collected. The viral genome was extracted, followed by polyacrylamide gel electrophoresis (PAGE), reverse transcription polymerase chain reaction (RT-PCR), and nucleotide sequencing. Samples were screened for rotaviruses by PAGE, and RVF and RVG genome banding patterns were not seen. Using RT-PCR, it was found that 9.4 % (8/85) of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
2
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 27 publications
2
8
2
3
Order By: Relevance
“…Regarding the circulation of RVA in canines and birds, the prevalence was 53% and 29%, respectively. Although in the Amazon region there are records of RVA, RVD, RVF and RVG that infect birds [57][58] and RVD in migratory birds [59], all were detected by RT-PCR assays differently from the present study which detected the RVA by RT-qPCR involving a variety of animal species.…”
Section: Discussioncontrasting
confidence: 93%
“…Regarding the circulation of RVA in canines and birds, the prevalence was 53% and 29%, respectively. Although in the Amazon region there are records of RVA, RVD, RVF and RVG that infect birds [57][58] and RVD in migratory birds [59], all were detected by RT-PCR assays differently from the present study which detected the RVA by RT-qPCR involving a variety of animal species.…”
Section: Discussioncontrasting
confidence: 93%
“…Next-generation sequencing of jejunal segments from 3-and 7-day-old chicks revealed multiple viruses in RSS-affected and unaffected chicks including avian nephritis virus, avian rotavirus, and gallivirus. Avian nephritis virus and avian rotavirus were previously reported in Brazil 8,9,23,24,28 and in other countries. 7,10,19,30,34,38,43,44 Similar to our findings, some researchers found avian nephritis virus in chicks at 3 and 7 days of age, but avian rotavirus was only detected from chicks in the second week of age, 8 diverging from our study that found avian rotavirus in chicks at 7 days of age.…”
Section: Discussionmentioning
confidence: 89%
“…In summary, all fecal samples from neotropical migratory birds were negative for PBV, ARV and AvRVA and only AvRVD was detected in Calidris pusilla as the only pathogen in these neotropical migratory birds. Nevertheless, it is valid to correlate the importance of the finding in the context of the Brazilian poultry industry, that is configured as an important segment of agribusiness exploring the probable risks of migratory birds as enteric virus reservoir for commercial poultry or vice versa due to previous detections of AvRVD (Avian Rotavirus D), AvRVA (Avian Rotavirus A), AvRVF (Avian Rotavirus F) and AvRVG (Avian Rotavirus G) in broilers in Brazilian territory (Bezerra et al, 2012;Luz et al, 2014;Silva et al, 2013;Mascarenhas et al, 2016).…”
Section: Investigation Of Enteric Viruses In the Feces Of Neotropicalmentioning
confidence: 99%